DISEASES RESULTING FROM DISORDERS OF MELOTONIN HORMONES AND THEIR TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The hormone melatonin plays a vital role in regulating the body's biological clock mechanisms, controlling the sleep-wake cycle, and coordinating numerous physiological processes. Disruption in the secretion of this hormone, which is synthesized by the pineal gland, leads to the development of various pathological conditions. This article analyzes the effects of both melatonin deficiency and excess on the human body, the spectrum of diseases arising from these conditions, and modern treatment approaches. The research results indicate that melatonin disruptions not only impair the sleep-wake cycle but also contribute to the development of metabolic syndrome, weakened immune function, increased risk of oncological diseases, and psychoneurological disorders. Modern therapeutic approaches include individualized dosing regimens, treatments based on chronobiological principles, and comprehensive therapy strategies.